Comparison of Body Composition Changes and Non-Contact Musculoskeletal Injuries Among Professional First-Class Cricket Pace Bowlers - Shukla, Maniah; Pandey, Vivek (Physical Education Theory and Methodology, 2023)
Background. Pace bowling is the most injury susceptible position in cricket due to repeated high intensity maneuvers. Previous studies on pace bowlers have considered anthropometric, biomechanical, and kinesiological factors for deciphering the injury etiology. Study purpose. The purpose of this study was to prospectively investigate the association of body composition parameters with the incidence of musculoskeletal injuries among pace bowlers in cricket. Materials and methods. A total of 44 healthy professional male pace bowlers (N=44; Age: 22.89±4.5 years; Height: 176±9 cm; Body weight: 76.34±8.09 kg; BMI: 21.4±3.1) were recruited from various cricket academies. They were assessed on anthropometrics, body composition, and aerobic fitness before the start of Indian cricket season (typically mid-September). Any non-contact sports injury accounting for significant time loss during the season was recorded followed by assessment of change in body composition status among injured and non-injured pace bowlers. Results. We found hamstring injury as the most prevalent injury (05/12). Lower back injury accounted for highest severity with time loss of 48 matches. Injured pace bowlers underwent higher training volume (hours/day; p=.009) prior to injury incidence, were significantly heavier, and had greater volume of total body water. All the pace bowlers gained significant amount of fat-free mass (FFM) from pre- to post-season. Conclusions. Higher training workload and higher body weight were associated with more injury risk among pace bowlers. Further research accommodating other predictive factors of body composition and psychomotor learning must be carried out to precisely predict injury risk among pace bowlers in cricket.